2019
DOI: 10.1167/iovs.18-26086
|View full text |Cite
|
Sign up to set email alerts
|

Visual Acuity in Pathological Myopia Is Correlated With the Photoreceptor Myoid and Ellipsoid Zone Thickness and Affected by Choroid Thickness

Abstract: PURPOSE. To quantify the thickness of the outer retinal sublayers and choroid in pathological myopia and examine associations between these factors and best-corrected visual acuity (BCVA). METHODS. The cohort was composed of 21 eyes with emmetropia and 70 eyes with high myopia (49 simple high myopia; 21 pathological myopia). Optical coherence tomography images were segmented to determine macular thicknesses of the choroid and the following outer retinal sublayers: outer plexiform layer (OPL), Henle fiber layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 30 publications
3
54
1
Order By: Relevance
“…Photoreceptor morphological and functional degeneration in myopia has been reported in previous studies 6- 13 and was hypothesized to be the main reason for visual impairment. 6 For instance, ERG examinations have documented decreasing bwave amplitudes in myopic eyes, indicating photoreceptor dysfunction.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…Photoreceptor morphological and functional degeneration in myopia has been reported in previous studies 6- 13 and was hypothesized to be the main reason for visual impairment. 6 For instance, ERG examinations have documented decreasing bwave amplitudes in myopic eyes, indicating photoreceptor dysfunction.…”
mentioning
confidence: 57%
“…Custom-developed software was used to analyze the OCT images. 13,16,17 Bennett's formula, t ¼ p 3 q 3 s, was used to correct the image magnification before calculating the thickness of outer retina and choroid. Based on the AL, the calculation shows the relationship between the OCT-imaged measurement and the actual scan range, where t indicated the actual scan length, p was the magnification factor of the OCT imaging system camera, q was the magnification factor related to the eye AL, and s indicated the original measurement value from the OCT image.…”
Section: Oct Measurement Of Outer Retinal and Choroidal Thicknessesmentioning
confidence: 99%
See 1 more Smart Citation
“…The position of the MCP was lower in the super-high myopia group than in the control group. Liu et al 27 and Ye et al 39 found that the Henle fiber layer and ONL, which comprise the largest portion of the retina, became thinner with the progression of myopia, and the inner nuclear layer showed the same changes. This change may explain why the position of the MCP declined.…”
Section: Discussionmentioning
confidence: 96%
“…This lack of a difference may be related to thickening of the outer plexiform layer (OPL) as myopia progresses. 27,39 Although the thickness of the Henle fiber layer and ONL decreases with the progression of myopia, the thickening of the OPL counteracts some of these effects, and the reduction in the inner nuclear layer, which affects the location of the MCP, does not influence the location of the DCP.…”
Section: Discussionmentioning
confidence: 99%